Topology and dynamics of a flow that has a non-saddle set or a W-set - Barge, Héctor; Sánchez-Gabites, Jaime J.; Sanjurjo, Jose M. R. (Topological Methods in Nonlinear Analysis, 2025)
The aim of this paper is to study dynamical and topological properties of a flow in the region of influence of an isolated non-saddle set or a $W$-set in a manifold.These are certain classes of compact invariant sets in whose vicinity the asymptotic behaviour of the flow is somewhat controlled.We are mainly concerned with global properties of the dynamics and establish cohomological relations between the non-saddle set and the manifold.As a consequence we obtain a dynamical classification of surfaces (orientable and non-orientable). We also examine robustness and bifurcation properties of non-saddle-sets and study in detail the behavior of $W$-sets in 2-manifolds.